OP0218 Elevated Serum BAFF is Associated with an Increased Risk of Developing A New Systemic Complication: Data from the Prospective ASSESS Cohort. (10th June 2014) - Gottenberg, J.E.; Seror, R.; Miceli-Richard, C.; Benessiano, J.; Devauchelle-Pensec, V.; Dieude, P.; Dubost, J.-J.; Fauchais, A.-L.; Goeb, V.; Hachulla, E.; Hatron, P.Y.; Larroche, C.; et al.
Abstract : Background: The validation of the EULAR Sjögren's syndrome Disease Activity Index (ESSDAI, composed of 12 domains) now allows to analyze the natural history of systemic disease activity in pSS. Serum levels of markers of B-cell activation were reported to be associated with the ESSDAI assessed on the same day and serum BAFF to be associated with history of lymphoma. However, their interest to predict new systemic complications has not been evaluated. Objectives: To determine the evolution of systemic disease activity in pSS and the interest of serum markers of B-cell activation as predictors of new systemic complications. Methods: The ASSESS cohort is a 5-year prospective cohort of 395 patients. Changes in systemic disease activity were analyzed by the occurence of a new domain of the ESSDAI, taking or not into account its level of activity and the biological domain. Baseline serum levels of markers of B-cell activation and BAFF were centrally assessed. Elevated BAFF was defined by a value ≥ mean+2 SD (1459.3 pg/ml) of 80 age and sex-matched controls. Results: At enrollment, after 1, 2 and 3 years of follow-up, the ESSDAI scores are already available in 383, 339, 231 and 178 patients. Between enrollment and the 1st year of follow-up, the 1st and the 2nd year, the 2nd and the 3rd year, a new domain of the ESSDAI was observed in 29.1, 33.2, and 31.7% of the patients, respectively (46.7% between enrollment and 3rd year). A new domain with moderate or high activity occurred in 9.4, 12.6 and 6.9% of the patients, respectively. A new moderate/high domain, except the biological domain, was observed in 4.8, 6.7 and 3.5% of the patients, respectively (8.9% between enrollment and 3rd year). Kappa and lambda free light chains of immunoglobulins and beta2-microglobulin were not associated with changes in systemic disease activity. An elevated serum BAFF level was significantly more frequently associated with the occurrence of a new moderate/high domain at 1 and 3 years (20.0% vs 7.7%, P=0.038 and 36.0% vs 15.9%, P=0.041, respectively), and of a new moderate/high domain except the biological domain at 3 years (24.0% vs 7.1%, P=0.031). Conclusions: Approximately half of the patients have changes in systemic activity and ∼10% develop a new relevant clinical complication after 3 years of follow-up. Baseline serum BAFF was associated with a higher risk of new systemic complications and could be used as a biomarker in clinical trials of new treatments of systemic complications of pSS. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4266